Development of Phyvar Media on Fission Reaction Material to Support Students' Spatial Intelligence - Prayoga, Adam Fori; Guntara, Yudi; Septiyanto, Rahmat Firman (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to determine the characteristics and feasibility of Physics In 3D Virtual Reality media on Fission Reaction material to support students' Spatial Intelligence. The research method used is Research and Development (R&D) with the Rowntree development model. The Rowntree model stages consist of 3 stages, namely the planning stage, development stage and evaluation stage. The subjects of this research consisted of 2 expert validation people, namely material and experts and limited trials on 36 students who were/had studied renewable energy subjects. The results of the material expert validation obtained a score of 97%. The validation results from media experts obtained a score of 94%. The assessment results from students as users were 85%. It can be concluded that the PHYVAR media in fission reaction material is very suitable for use and supports students' spatial intelligence.